Financial Surveillance Strategy : Progress Report. (Policy Papers; Policy Paper ;, 2013)
This note provides background to the informal Board briefing on the one-year progress in implementation of the FSS. The Board will have the opportunity to review progress in implementing the FSS in the context of the 2014 TSR and the 2014 review of the Financial Sector Assessment Program (FSAP), as well as through periodic reports to the International Monetary and Financial Committee and the semi-annual work program.